Diachronic Emergence of Zipf-like Patterns in Construction-Specific Frequency Distributions: A Quantitative Study of the Way Too Construction - Quentin Feltgen (Lexis: Journal in English Lexicology)
The linguistic constituents that come to express path are often co-opted into more abstract schematic constructions through a diachronic process known as constructionalization. This applies to the way too intensifier construction, whose origin I retrace to a former away too construction. Moreover, the emergence of a schematic construction is associated with an evolution of its type frequency (the total number of different linguistic units that fill the free slot of the construction). Although the evolution of the token frequency throughout a constructionalization process has already been studied from a quantitative perspective, the type frequency has not received such an empirical characterization. I show that the type and token frequencies are related with one another through a Zipf’s law, whose coefficient varies with time, and which sorts the different types according to their collocate frequency in a way that is robust both across time and across varieties of English.